👤
Dogarudana
a fost răspuns

(x-1)+(2x-2)+(3x-3)+...+(9x-9)=90

Răspuns :

x+2x+3x+....9x-(1+2+3+...9=90
x(1+2+3+..9 -(9×10)/2=90
x(9×10)/2=90+45
x×45=135
x=135/45=27/9=3
Alitta
=> ... = (x-1)+2(x-1)+3(x-1)+...+9(x-1) = (x-1)(1+2+3+...+9)=
                                                            = (x-1) · (9·10:2)=
                                                            = (x-1) · (9·5) =
                                                            = (x-1) · 45 =
                                                            = 45 · (x - 1)  !!!
                         deci    
45(x-1) = 90
                                         x - 1 = 2
                                              x = 3 .